Renal impairment is an independent predictor of adverse events post coronary intervention in patients with and without drug-eluting stents - Shaw, J.; Andrianopoulos, N.; Duffy, S.; Walton, A.; Clark, D.; Lew, R.; Sebastian, M.; New, G.; Brennan, A.; Reid, Christopher; Ajani, A. (2008)
Renal impairment (RI) is known to be an independent risk factor for the progression of cardiovascular disease. Its impact, however, on the outcomes in patients undergoing percutaneous coronary intervention (PCI) especially in the era of drug-eluting stents (DES) is not well known. We analysed data from patients undergoing PCI from April 1, 2004, to September 30, 2006, who were part of the Melbourne Interventional Group registry. RI was defined as an estimated glomerular filtration rate (eGFR), calculated using Cockcroft-Gault formula, of <60 ml/min. We compared outcomes at 30 days and 12 months in patients with and without RI. Four thousand one hundred ninety-five patients (3043 male) with an average age 65±12 years (mean±S.D.) underwent PCI. Twelve-month follow-up was available in 3963 (95%) patients, and these were included in the analysis. One thousand twelve patients (26%) had RI; of these, 608 (60%) presented with an acute coronary syndrome. Both 30-day major adverse cardiac events (MACE), 9.1% vs. 4.6% (P<.01), and all-cause mortality, 4.5% vs. 0.7% (P<.01), were significantly higher in those with RI compared to those without RI. Twelve-month mortality (8.8% vs. 1.7%, P<.01) and MACE (19.7% vs. 10.3%, P<.01) were also significantly higher in those with RI. In multiple regression analysis, RI was an independent predictor of 12-month MACE [OR 2.0 (CI 1.6-2.6), P<.01]. RI is an independent predictor of 30-day and 12-month MACE and death after PCI in patients with stable and unstable coronary syndromes, even with widespread use of DES. eGFR should be used to help risk-stratify patients undergoing PCI. © 2008 Elsevier Inc. All rights reserved.